Identidades Docentes y Prácticas Pedagógicas Que Promueven la Interculturalidad en Contextos Escolares de Alta Migración - Aguilera-Valdivia, M (Universidad Nacional Autonoma de Mexico, 2023)
This article presents results for my research on teaching identity and pedagogical practices that promote interculturality. I conducted this upon four professors working at educational institutions within the metropolitan region of Santiago de Chile, an area containing a high concentration of migrant students. The study’s goal was to explore how teaching identities are linked to pedagogical practices that promote interculturality. We used a qualitative methodology with a biographic-narrative focus and an ethnographic approach to the classroom. The professors’ identity characteristics were reflected in pedagogical performative practices promoting interculturality within school communities which lack or receive very little and/or inefficient support from the government in the development of this subject. These characteristics are rooted in the lived biographical experiences of the professors within their family, school, and geographical environments, as framed by conditions of socioeconomic poverty © 2023,Perfiles Educativos. All Rights Reserved.